(untitled) (Biological Sciences - PJSIR, 2002)
Thiabendazole and benomyl fungicides after post harvest treatment, were monitored in samples of apples and citrus fruits collected from the main fruit markets of Karachi during the year 1998-99 and 1999-2000. A total of 150 samples (75 samples of each commodity) were screened out of which 82 samples were found to contain either of the tstudied fungicides. Only in 8 samples, Codex exceeded maximum residue limits (MRL’s) while 74 samples contained residues well within permissible limits.